O Campo profissional do executive coaching no Ceará: perfil, atuação e demanda - Leite, Ana Maria Andreazza Araújo (2015)
Coaching is increasingly used by organizations to develop their leaders. The number of academic publications on the subject is also increasing. However, in Brazil and Ceará, academic production still has many theoretical and empirical research gaps on executive coaching, among them the understanding of the constitution of this professional field in Ceará. This work has as main objective to identificate the professional field of executive coaching in Ceará, in terms of the profile and performance of coaches as well as the demand of the contracting organizations. To this end, are set three specific objectives: 1) to investigate the executive coach profile characteristic, with regard to their skills and training; 2) to examine the performance of the executive coach, from the perspective of professional and contracting organizations; and 3) characterize the demand of organizations for the work of the executive coach. This is a research characterized as descriptive qualitative, with primary data collection method performed through semi-structured interviews and questionnaires with 10 coaches, 10 coachees and 8 contracting organizations, setting triangulation data. Content analysis allowed the observation that the professional field of executive coaching in Ceará is still not well defined, although there is concordance among respondents about the profile and performance of the coaches as well as the demand for their work. Regarding the profile of the executive coach, greater consistency was evidenced on the required skills of knowledge in coaching, management and behavior, as well as the ability to establish trust and the need for a longer and deeper formation. Concerning the performance of the executive coach it is evident the need for regulation of activities with the existence of a code of ethics based on agreed principles and observed by professionals working in the field. On the professional principles that should be observed in the performance of coaches , there is a reversal in the hierarchy of importance between the interviewees. Meanwhile, from the perspective of coachees and organizations, greater importance was given to the principle of secrecy and confidentiality. This was the least cited by the coaches. Regarding the demand for the coach's work, it was more evident in the organizations performance improvement and leadership development. For coachees, greatest demand is improving relationships and emotional balance. A challenge for coaches is the ability to meet the different demands of people and organizations, as these seek results based on strategic objectives, while those seeking more balance between personal and professional life, in order to be happier and, consequently, fulfilling.